Biopsy-proven acute tubulointerstitial nephritis in patients treated with immune checkpoint inhibitors: a pooled analysis of case reports - Esposito, Pasquale; Bottini, Annarita; Lecini, Elvina; Cappadona, Francesca; Piaggio, Michela; Macciò, Lucia; Genova, Carlo; Viazzi, Francesca (Frontiers in Oncology, 2023)
Introduction Acute kidney injury (AKI) in cancer patients receiving immune checkpoint inhibitors (ICIs) may recognize multiple causes. Here, we reviewed cases of biopsy-proven acute tubulointerstitial nephritis (ATIN) to describe the clinical characteristics and outcomes of this condition. Method We conducted a pooled analysis of clinical cases of ICI-related biopsy-proven ATIN up to 1 May 2022. We collected data on clinical characteristics, AKI, biopsy findings, laboratory examinations, and renal outcomes. Results Eighty-five patients (61.4 ± 19 years, 56 male) were evaluated. Melanoma was the most prevalent diagnosis (51%), followed by non-small cell lung cancer (30%). ICI treatment consisted of PD-1, PDL-1 (nivolumab, pembrolizumab, atezolizumab), and CTLA-4 inhibitors (i) (ipilimumab) or combination PD-1i+CTLA4i. Renal toxicity developed after a median of four cycles of therapy. Fifty-one patients (65.5%) developed the most severe form of AKI- stage 3, including five patients requiring dialysis. All the 19 patients treated with dual ICI blockade developed AKI-stage 3, compared with 29 patients out of the 60 receiving a single agent (p<0.001). Most events were managed with corticosteroids associated with ICI withdrawal. In 15 patients ICI was restarted, but in six (40%) AKI recurred. Overall, 32 patients (40%) presented a complete renal recovery, which chance was inversely associated with dual ICI blockade (OR 0.15, 95CI 0.03-0.7, p=0.01). Conclusion ICI-related ATIN may develop late after the therapy initiation, presenting as severe AKI, particularly in patients with dual ICI blockade. Although this complication may be partially reversible, concerns remain about the renal function sequelae and the possibility of restarting ICI treatment.